Virtual reality-based distraction on pain, performance, and anxiety during and after moderate-vigorous intensity cycling - Wender, C. L. A.; Tomporowski, P. D.; Ahn, S. J. C.; O'Connor, P. J. (Physiology & Behavior, 2022)
Purpose To determine whether increased visual perceptual load (PL) within an immersive virtual environment may help explain previously shown pain-relieving effects of virtual reality (VR) during high intensity cycling.